Institutionalisierung der Mediation (assen) in Japan - Baum, Harald; Schwittek, Eva (Zeitschrift für Japanisches Recht, 2009)
As was pointed out by the authors in an article in J.Japan.L. 26 (2008), there are two basic types of consensus-oriented settlement procedures in modern Japan: the courtrelated conciliation procedures (chôtei) that were explained in J.Japan.L. 27 (2009), on the one hand, and the various kinds of ADR procedures (assen) offered by private institutions on the other. In the present article, the authors analyse the recent institutionalisation of ADR procedures by legal regulation. ADR procedures have a longstanding and varied tradition in Japan, but were until recently not underpinned legally. The attempt to increase the quality and transparency of ADR procedures by institutionalising them is a fundamental component of the comprehensive reform of the Japanese judicial system that plays a major role in the socio-political discussion of the current decade. The “Act on Promotion of Use of Alternative Dispute Resolution” (ADR law) came into effect on April 1, 2007. It is complemented by an executive order of the Ministry of Justice and by a Cabinet order. The law, which comprises 34 articles, aims at creating a legislative framework to make ADR procedures more efficient by integrating them at least partially in the ordinary jurisdiction; in addition, it aims at making them more reliable and transparent by introducing a system of certification for mediators. By this means, parties of a conflict should be enabled to choose the procedure of conflict resolution that best meets their needs. The introductory remarks of the law stress the voluntariness and reconciliatory nature of the procedure. The central point of the ADR law is the certification of institutions for the settlement of disputes. However, the vocational training of mediators is not regulated; instead, the law is restricted to detailed provisions on the premises and procedure of certification. The law principally provides that a natural or juridical person that carries out conflict resolution procedures regularly can obtain a certification if it complies with certain requirements and if there are no personal reasons for exclusion. The participation in a procedure conducted by a certified ADR institution is very advantageous for the parties of a conflict. For example, prescription is interrupted during the duration of the procedure if a consensus is not reached. Also, a pending action is discontinued during the duration of ADR proceedings. The new regulation brings about a professionalization and especially a commercialisation of alternative dispute resolution. Within the certification system, this form of dispute resolution can be seen as a service that (deliberately) competes with the hitherto existing extensive monopoly for legal advice held by attorneys. Within the first two years since the coming into effect of the ADR law, more than 40 ADR institutions with various specialisations have been certified. The coming into effect of the law has implemented an essential reform for the improvement of granting of legal remedies, at least in its basic form. The practical acceptance and effects of the law are to be evaluated after five years of its coming into effect. In view of the lack of regulation of procedural problems, it is to be expected that the law will be revised and amended substantially within the process of evaluation. For example, especially the planned codification of procedural regulations and the inclusion of the enforceability of the attained agreement have not been accomplished. It is planned to expedite the cooperation between ADR providers in order to further inform the population about the existing possibilities of ADR, to establish central ADR centres and to provide for vocational trainings for mediators. Also, there are plans to certify and train mediators subject-specifically, e.g. to enact laws that regulate the process of certification and the employment in ADR procedures separately for the members of each occupational group.